Spurious correlations in simultaneous EEG-fMRI driven by in-scanner movement - Fellner, M.-C.; Volberg, G.; Mullinger, K.J.; Goldhacker, M.; Wimber, M.; Greenlee, M.W.; Hanslmayr, S. (Elsevier, 2016)
Simultaneous EEG-fMRI provides an increasingly attractive research tool to investigate cognitive processes with high temporal and spatial resolution. However, artifacts in EEG data introduced by the MR-scanner still remain a major obstacle. This study employing commonly used artifact correction steps shows that head motion, one overlooked major source of artifacts in EEG-fMRI data, can cause plausible EEG effects and EEG-BOLD correlations. Specifically, low frequency EEG (<20 Hz) is strongly correlated with in-scanner movement. Accordingly, minor head motion (<0.2 mm) induces spurious effects in a twofold manner: Small differences in task-correlated motion elicit spurious low frequency effects, and, as motion concurrently influences fMRI data, EEG-BOLD correlations closely match motion-fMRI correlations. We demonstrate these effects in a memory encoding experiment showing that obtained theta power (~3-7 Hz) effects and channel-level theta-BOLD correlations reflect motion in the scanner. These findings highlight an important caveat that needs to be addressed by future EEG-fMRI studies. Keywords: